Trends, Practices, and Technology Issues in Early Childhood Education in Korea - Bae, Ji Hi (My University, 2012)
Education for young children has always been valued in Korea. Korean people believe that children should be educated and cherished from the time of conception. Prenatal education thus is greatly valued. During early childhood, character education and the formation of basic, everyday life habits are emphasized. This is well-reflected in a famous Korean saying: “Habits formed at three last until eighty.” Korean early childhood education aims to promote the development of the whole child. In practice, an integrated curriculum with a focus on diverse activities that reflect children’s developmental stages, interests, and everyday life is implemented. Respect for children, child-centered educational philosophy, play-oriented activities, interactions with their environments, peers, and teachers are all highly valued. Children are encouraged to actively participate in the learning process with teacher guidance, and diverse educational programs and approaches for young children are adopted and applied.